2020
DOI: 10.1177/0190272519887719
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of Foreigners Negatively Predicts the Prevalence of Xenophobic Hate Crimes within German Districts

Abstract: Statistics show that the increase in the number of refugees to Germany since 2015 was accompanied by an increase in xenophobic hate crimes. We deduced rivaling predictions from intergroup contact and intergroup threat theories that could explain the occurrence of xenophobic hate crimes. By combining structural data of the 402 German districts with the 2015 police crime statistics, we found evidence to support our predictions that aligns with intergroup contact theory: the higher the proportion of foreigners in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 20 publications
1
20
2
Order By: Relevance
“…Contributing to emergent literature that focuses on processes of change (Geschke, 2007; Van Zalk, Kotzur, Schmid, Al Ramiah, & Hewstone, 2020; Wölfer et al, 2016), as opposed to examining the relationship between contact opportunities and prejudice cross-sectionally, we found that prejudice can rise with increased intergroup contact opportunities. These findings contradict many studies that show that contact opportunities, measured as the presence of minority members or ethnic composition within a geographical region, are typically associated with reduced levels of prejudice (e.g., Brune et al, 2016; Hewstone & Schmid, 2014; Lubbers et al, 2006; Oliver & Wong, 2003; Pettigrew, 1997; Wagner et al, 2006, 2020), including rare empirical examples that investigated change of contact opportunities (Geschke, 2007; Van Zalk et al, 2020). Instead, our results support a few studies that found the opposite (Green et al, 2010; Quillian, 1995).…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Contributing to emergent literature that focuses on processes of change (Geschke, 2007; Van Zalk, Kotzur, Schmid, Al Ramiah, & Hewstone, 2020; Wölfer et al, 2016), as opposed to examining the relationship between contact opportunities and prejudice cross-sectionally, we found that prejudice can rise with increased intergroup contact opportunities. These findings contradict many studies that show that contact opportunities, measured as the presence of minority members or ethnic composition within a geographical region, are typically associated with reduced levels of prejudice (e.g., Brune et al, 2016; Hewstone & Schmid, 2014; Lubbers et al, 2006; Oliver & Wong, 2003; Pettigrew, 1997; Wagner et al, 2006, 2020), including rare empirical examples that investigated change of contact opportunities (Geschke, 2007; Van Zalk et al, 2020). Instead, our results support a few studies that found the opposite (Green et al, 2010; Quillian, 1995).…”
Section: Discussioncontrasting
confidence: 92%
“…Contact opportunities do not necessarily ensure actual contact or reductions of prejudice (Van Dick et al, 2004). Nonetheless, contact opportunities, operationalized as the presence of minority members within a geographical region, are often associated with reduced prejudice (e.g., Brune et al, 2016; Hewstone & Schmid, 2014; Kaufmann & Harris, 2015; Lubbers et al, 2006; Oliver & Wong, 2003; Pettigrew, 1997; Wagner et al, 2006, 2020). However, although contact opportunities have been repeatedly shown to be associated with less prejudice, some studies found the opposite relation (e.g., Green et al, 2010; Putnam, 2007; Quillian, 1995).…”
Section: Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is not surprising that the challenges of forced migration have pre‐occupied national and international politics, affected national election campaigns and polarized receiving societies. The reactions to refugee arrivals by residents of receiving societies range from hostility, rejection (e.g., Benček & Strasheim, ) and violence (Wagner, Tachtsoglou, Kotzur, Friehs, & Kemmesies, ) to active support and helping (Ahrens, ; Stürmer & Siem, ). The variety of these reactions has been amply covered by mass media and discussed in public discourse.…”
Section: The Perspective Of Residents and Refugeesmentioning
confidence: 99%
“…Nativist and nationalist movements are gaining renewed traction (Bouie, ; Infratest dimap, , ). In Germany, these developments are for instance reflected in the rise in the electorate for the right‐wing party AfD propagating nationalist policies (Goerres, Spies, & Kumlin, ), and physical assaults directed toward refugee‐immigrant‐related targets (e.g., Mut gegen rechte Gewalt, ; Wagner, Tachtsoglou, Kotzur, Friehs, & Kemmesies, ). In the United States, Donald Trump was elected as president with a strong focus on anti‐immigrant sentiments, symbolized in his demand to build a wall at the U.S.—Mexican border.…”
Section: Putting Contact Into Context: Germany and United Statesmentioning
confidence: 99%